The effect of substrate availability on behavioural and physiological indicators of welfare in the African cichlid (Oreochromis mossambicus) - Galhardo, Leonor (2012)
Male African cichlids (Oreochromis mossambicus) establish territories on the substrate upon which spawning pits are dug, thus attracting females. The substrate, therefore, plays a very significant role in its lifecycle. The effects of substrate access on behaviour and physiology in captivity were assessed. Mixed-sex, all-male and all-female groups were observed for five days, with and without substrate. Social patterns, behaviour directed towards the substrate, locomotor activity and spatial behaviour were recorded, and haematocrit, plasma cortisol and glucose levels were measured. Substrate inclusion saw a significant increase in behavioural diversity, sexual behaviour of dominant males in mixed groups, pit digging and territoriality whereas a lack of substrate was characterised by increased chafing and inactivity. Vacuum-pit digging was also observed. Frequency of aggression did not differ significantly and female behaviour was not affected by the presence of substrate. For both sexes, no differences in cortisol and glucose levels were found between the two treatments, but haematocrit increased with substrate. The key role played by substrate in territorial males is consistent with the behavioural and physiological data reported. In the absence of substrate, decreased territorial behaviour is contrasted with similar levels of aggression, cortisol and glucose; all of which are suggestive of a stress-related context. Moreover, the exhibition of vacuum activities is a signal that behavioural needs are not being met and may be some form of coping mechanism. These findings, taken in conjunction with the variations in behavioural diversity and inactivity, suggest that the welfare of male cichlids may be adversely affected by the absence of substrate.